Soil Amendments for Sustainability : Challenges and Perspectives. - Rakshit, Amitava; Sarkar, Binoy; Abhilash, Purushothaman (Milton : Chapman and Hall/CRC, 2018)
This book focuses on the pros and cons of amendment materials to restore the functioning of soil resources. It presents a holistic overview on affected land revitalization, clean up and revegetation using these amendments that could be implemented in the long term management of the soil-plant-atmosphereanimal continuum.
3.6.2.1 The 4R Nutrient Stewardship Concept3.6.2.2 Right Source at the Right Rate, Time, and Place; 3.6.2.3 Principles Supporting Practices; 3.6.2.4 Application of Nutrient Expert® (NE) Software; 3.6.3 Minimizing Nutrient Transport from Agricultural Fields; 3.6.3.1 Leaching Loss of Nutrient; 3.6.3.2 Soil Erosion, Conservation Tillage, and Carbon Sequestration; 3.6.3.3 Field Buffer Strips; 3.7 Conclusions; References; Chapter 4: Digital Soil Science for Identification of Problem Soil Characteristics; 4.1 Introduction.
4.2 Use of Space- and Airborne Remote Sensing for Identification of Problem Soils.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY & ENGINEERING / Agriculture / General; Biochar; Carbon Sequestration; Fly Ash; Phosphate Rock; Soil Amelioration; Soil Amendments; Soil amendments; Sustainable horticulture